A case of endonasal balloon‐assisted dacryoplasty after failure of endonasal dacryocystorhinostomy. Issue 9 (19th May 2020) - Indelicato, Pietro; Vinciguerra, Alessandro; Giordano Resti, Antonio; Trimarchi, Matteo
Abstract: Endonasal balloon‐assisted dacryoplasty is a minimally invasive technique that uses a high‐pressure balloon catheter introduced into the lacrimal pathway through the nasal fossa into the neorhinostomy to treat recurrent epiphora after primary dacryocystorhinostomy. This procedure can be considered to be a reliable technique in patients unfit for general anesthesia. Abstract : Endonasal balloon‐assisted dacryoplasty is a minimally invasive technique that uses a high‐pressure balloon catheter introduced into the lacrimal pathway through the nasal fossa into the neorhinostomy to treat recurrent epiphora after primary dacryocystorhinostomy. This procedure can be considered to be a reliable technique in patients unfit for general anesthesia.